From Origins to Adaptation: Typologies of Joglo Houses After Translocation in Ngloro Village, Gunungkidul – Yogyakarta - Yusfan Adeputera Yusran; Ananda Weningtyas Handoyono; Agung Murti Nugroho (Local Wisdom Jurnal Ilmiah Kajian Kearifan Lokal, 2026)
The development of the times and the pressure of social change have threatened the survival of vernacular architecture, including the Joglo house as a Javanese cultural heritage. One form of ex-situ preservation carried out by the Ngloro Village community is to move the Joglo house to a new location. This translocation process not only involves the physical movement of the building but also triggers changes in its visual and spatial form. This study aims to identify the typology of post-translocation Joglo houses in Ngloro Village, Gunungkidul Regency, Yogyakarta. The method employed is a qualitative-descriptive approach, utilizing a case study of 14 translocated Joglo houses. Data collection was conducted through direct observation and non-structured interviews, which were then analyzed typologically and contextually using the theory of adaptive reuse. The results of the study indicate that the adaptation process resulting from the translocation of Joglo houses has created new typologies, including changes in roof shape, facade, floor materials, foundations, orientation, building position, and room functions. Roof typology is dominated by a combination of Joglo–Limasan–Pelana roofs, while core structures such as saka guru and tumpang sari are retained. Adaptation to the new location context and functional needs results in a transformation that preserves the fundamental value of the building. Therefore, relocated Joglo houses do not represent heritage degradation but rather the adaptive and sustainable evolution of traditional architecture.